Air permeability of thermally modified hemlock wood - Liu, Yaohui (Les (Ljubljana), 2022)
Western hemlock (Tsuga heterophylla) is a prevalent coastal species in British Columbia (BC). Its wood has a high potential for thermal modification, a process that can affect numerous physical properties, including air permeability. The current study investigates the longitudinal air permeability of hemlock wood modified at three temperature levels, 170 °C, 212 °C, and 230 °C, and a two-hour treatment length. Permeability values obtained using Darcy’s law and the water-falling volume displacement method were positively correlated with treatment temperature up to 212 °C, after which the permeability decreased slightly. ANOVA followed by the Duncan test revealed that thermal treatment at 212 °C and 230 °C significantly increased air permeability, whereas it was insignificant at 170 °C.
Keywords: longitudinal air permeability; specific permeability; specifična permeabilnost; termična modifikacija; thermal modification; Tsuga heterophylla; vpliv temperature; vzdolžna plinska permeabilnost; western hemlock; wood; zahodna čuga